PENGENDALIAN KUALITAS COLORED FIBER DENGAN METODE SEVENTOOLS DI PT. XYZ - Sufrotun Khasanah; Hurun’in; Beta Arya Ash Shidik; Rivaldo Rizky Fadila (JERA : Journal of Engineering Research and Application, 2023)
XYZ is the first fiber optic factory in Kendal to start operating in 2021. The main production from PT. XYZ is an optical cable and underwater cable or commonly called a submarine cable. One of the vital problems experienced by PT. XYZ in starting its production operations is on quality control issues. PT. XYZ is in the stage of looking for appropriate quality standards and can be used to compete with its competitors. The control method used to explore and identify unqualified products in the fiber coloring process is the seventools method. Seventools is able to present data in detail and accurately with the seven tools in it, another advantage that seventools has is that it is easy to understand and implement. The purpose of this research is to find out how to control, the factors that cause defects and how to apply the seventools method to the quality of colored fiber at PT. XYZ. The results of the study using seventools related to line coloring and colored fiber, preventive and countermeasures that can be taken are to recheck and rewind unqualified products, create and install technical requirements in the production area to make it easier for operators to identify standardized products made and provide paint roller machines to maintain color quality, separate storage shelves for qualified and unqualified products and cultivate 5S in operators.